Analisis Kebijakan DPRD Kota Medan Tentang BPJS Kesehatan Perspektif Ekonomi Islam - Fauja, Zalika; Marliya, Marliyah (Universitas Muhammadiyah Metro, 2023)
It is a must for everyone in Indonesia to have health insurance in life, one of which is to become a member of the Social Security Administering Body (BPJS). National Health Insurance (JKN) is one of the policies to support the implementation of social development programs in Indonesia. This is in accordance with the mandate of the 1945 Constitution, where the state provided social protection to achieve social justice.This study discusses how the Medan City DPRD's policy on BPJS health from an Islamic economic perspective, using descriptive qualitative methods, the research was conducted at the secretariat of the Medan City DPRD. There are several public aspirations regarding BPJS health, so there is a need for internal policies. And some policy suggestions so that BPJS in the city of Medan is in accordance with Islamic teachings to avoid gharar, maysir (gambling) and usury and the community evenly gets national health insurance.